Analisis Sektor Unggulan Provinsi Sumatera Utara Tahun 2020-2023 - Sandra, Indah Kartika; Varwasih, Mia Wananda; Nofitasari, Rahmi (Universitas Galuh, 2025)
North Sumatra Province is the ninth largest province in Indonesia. Therefore, the development of this very large area requires appropriate development program steps. One method that can be used in planning the economic development of a region is to determine the leading sectors in the region that are further developed without ignoring other sectors. The purpose of this study is to determine the leading sectors in the North Sumatra economy that can be used as a basis for designing economic development strategies in North Sumatra Province. This analysis is based on secondary data (time series), including North Sumatra's GRDP (Gross Regional Domestic Product) and Indonesia's GDP (Gross Domestic Product) in the period 2020-2023. This study uses a quantitative approach with LQ (Location Quotient), DLQ (Dynamic Location Quotient), and Klassen Typology Analysis. The results of the study show that the sectors that grew rapidly in North Sumatra during the period 2020-2023 include the water supply, waste management, waste, and recycling sectors; wholesale and retail trade sectors; motor vehicle and motorcycle repair sectors; and the real estate sector. Meanwhile, the agriculture, forestry, and fisheries sectors; construction sectors; and the transportation and warehousing sectors are not leading sectors that are growing rapidly, but remain important foundation sectors for the North Sumatra economy. In order for these sectors to become leading sectors, government policy intervention is needed to increase their growth.